Tras la estela de Corte-Real. El poema Sepúlveda e Lianor en la memoria de Lope de Vega, Cervantes, Calderón, Solórzano Pereira y Tirso de Molina - Alves, Hélio (2014)
Although forgotten and even maligned by literary criticism and history since the 19th century, Jerónimo Corte-Real (?-1588) was a Portuguese poet of great importance and influence in the Spanish Golden Age. The author of large poems about Portuguese expansion in the East and the battle of Lepanto which had a significant impact in Spain, Corte-Real also composed another poem about a much more domestic affair, the story of the unfortunate marriage between Lianor and Manuel Sepúlveda, that would be published only in 1594, in Lisbon, a few years after the poet’s death. This article argues that, although never translated into Spanish, the poem Sepúlveda e Lianor was read at the highest level, as witnessed by the works of Solórzano Pereira and Tirso de Molina, and even became part of the poetic memory of Cervantes, Lope de Vega and Calderón. Intertextuality with Sepúlveda e Lianor, apparently mediated by Portuguese texts about the poetic canon of the neighbouring country (the case of Pedro de Mariz is studied here), shows the need to change substantially the interpretation given to some texts written by these major authors of Spanish literature.